Pengaruh Teripang Emas (Stichopus Hermanii) pada Remodeling Ekspansi Sutura Maksila Terhadap Lebar Palatal Menggunakan Analisis Sefalometri - Anydya Putri; Noengki Prameswari; Budi Handayani (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2015)
Background: Maxillary expansion device causing mechanical pressure to open the maxillary suture which causes inflammation and bone remodeling around the area. Stichopus hermanii is known to contain flavonoid, chondroitin sulfate, omega 3 (EPA and DHA) and dermatan sulfate which is used to inhibit inflammatory process, increase bone metabolism and mineralization, and bone remodelling. Purpose: The aim of this experiment is to know the effect of Stichopus hermanii on maxillary suture remodeling expansion to palatal width using cephalometric analysis. Materials and Methods: Experimental units used was 24 male Caviacobaya divided into 4 groups (n=6). Group K(-) is negative control. Helical spring was applied to and activated in the other 3 groups for 10 days. Group K(+) was given 2% NaCMC gel, both group P1 and P2 was given 3% Stichopus hermanii gel. Group P2 werealso given retention period for 10 days after activation period. Cavia cobaya were then decaputated and observed for the palatal width changes. The data was analyzed with One Way ANOVA test continued with LSD test. Result: The result of ANOVA test showedsiginficant differences among the treatment groups p=0,000 (p<0,05). LSD test showed significant differences between group K(-) and K(+) (Sig. 0,000), K(-) and P1 (Sig. 0,000), K(-) and P2 (Sig. 0,000), K(+) and P2 (Sig. 0,020) and group P1 and P2 (Sig. 0,036).Conclusion: 3% Stichopus hermanii gel has effect on maxillary suture remodeling expansion to palatal width use cephalometric analysis and combination of Stichopus hermanii with 10 6days retention period resulting the widest palatal width.